1996
DOI: 10.1111/j.1472-765x.1996.tb01191.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of short-chain fatty acids on the size of enteric bacteria

Abstract: The size of Escherichia coli and Salmonella enteritidis PT4 cells was measured using both transmission electron micrographs and image analysis. Incubation in the presence of formic and propionic acids resulted in larger cells, possibly as a result of DNA inhibition, with no apparent damage to the cell membranes. Bacteria incubated with propionic acid were more resistant to shrinkage after fixation, possibly as a result of altered phospholipid and fatty acid composition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 16 publications
1
8
0
Order By: Relevance
“…when grown in a yeast extract minimal medium at pH 5 with approximately 50 mmol l –1 citric acid (Cherrington et al . 1991b; Thompson and Hilton 1996).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…when grown in a yeast extract minimal medium at pH 5 with approximately 50 mmol l –1 citric acid (Cherrington et al . 1991b; Thompson and Hilton 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Further, using transmission electron microscopy, other authors have found no evidence of OM disruption in E. coli and Salmonella spp. when grown in a yeast extract minimal medium at pH 5 with approximately 50 mmol l ±1 citric acid (Cherrington et al 1991b;Thompson and Hilton 1996).…”
Section: Discussionmentioning
confidence: 99%
“…For example, unlike propionate and butyrate, acetate can be transported into the cell in the dissociated and undissociated forms (Axe and Bailey 1995). Acetate may therefore act as an uncoupler and dissipate the proton motive force (Axe and Bailey 1995) while propionate has been shown to inhibit DNA synthesis in Escherichia cofi (Thompson and Hinton 1996;Cherrington el af. 1990).…”
Section: Cell Invasionmentioning
confidence: 99%
“…Poimenidou et al (2016) reported that the b * values of lettuce, after storage for 6 days, were 37.1, 22.5, and 24.1 following washing with 300 ppm sodium hypochlorite, 2% lactic acid, and vinegar (6% AA), respectively. These phenomena may be attributed to the direct damage of the lettuce surface by oxidizing agents, such as ozone, which causes lipid oxidation in the cell envelope (Khadre, Yousef, & Kim, 2001), unlike organic acids inducing irreversible denaturation of intracellular acid-sensitive proteins (Ricke, 2003) without inducing membrane damage (Cherrington, Hinton, Pearson, & Chopra, 1991; Thompson & Hinton, 1996).…”
Section: Resultsmentioning
confidence: 99%